2018
DOI: 10.1186/s12894-018-0389-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of total ureterectomy with ileal-ureteral substitution treatment for ureteral cancer: a single-center experience

Abstract: BackgroundTo explore the feasibility and long-term outcomes of renal preservation in a retrospective cohort of patients with ureteral urothelial carcinoma undergoing total ureterectomy with ileal-ureteral substitution.MethodsA retrospective review of the data from patients treated with total ureterectomy with ileal-ureteral substitution from 1988 to 2016 was performed. The pre-operative oncological status, long-term oncological outcome, long-term renal functional outcome, early and late complications were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Last, ileal substitution is an option for those with more extensive ureteral involvement. A more recent single center retrospective review from Ou et al [ 52 ] identified 80 patients that underwent ileal ureter creation for UTUC and 2- and 5-year CSS were 87.55% and 75.0%, respectively.…”
Section: Nephron-sparing Surgical Resectionmentioning
confidence: 99%
“…Last, ileal substitution is an option for those with more extensive ureteral involvement. A more recent single center retrospective review from Ou et al [ 52 ] identified 80 patients that underwent ileal ureter creation for UTUC and 2- and 5-year CSS were 87.55% and 75.0%, respectively.…”
Section: Nephron-sparing Surgical Resectionmentioning
confidence: 99%
“…Furthermore, ureteral urothelial carcinoma is usually treated by a long-segment or even total ureterectomy under the circumstances where ureteric substitution with intestine could be desirable. 13 In addition, some rare congenital ureteral abnormalities, such as ureteral ectopia, ureteral agenesis or absence, or long congenital ureteral stenosis, that are unsuitable for more conservative reconstructive techniques, might require ureteral substitution to salvage renal function. Additional indications might include renal transplantation with ureteral necrosis or rejection.…”
Section: Indications Of Intestinal Interpositionmentioning
confidence: 99%
“…Other indications might include recurrent intractable renal lithiasis, in that the wider caliber of intestinal ureter can facilitate the passage of calculi so as to alleviate the secondary symptoms of ureteral obstruction. Furthermore, ureteral urothelial carcinoma is usually treated by a long‐segment or even total ureterectomy under the circumstances where ureteric substitution with intestine could be desirable . In addition, some rare congenital ureteral abnormalities, such as ureteral ectopia, ureteral agenesis or absence, or long congenital ureteral stenosis, that are unsuitable for more conservative reconstructive techniques, might require ureteral substitution to salvage renal function.…”
Section: Indications Of Intestinal Interpositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distal SU with ureterocystoneostomy has lower recurrence rates compared to SU of the proximal ureter with ureteroureterostomy [1] , [3] . Complete resection of the ureter and substitution (eg, with ileum) is technically feasible but should be reserved for low-risk tumors in highly selected cases as it is only supported by low-level evidence [4] .…”
mentioning
confidence: 99%